Development of Flash Card Learning Media Assisted by Augmented Reality on the Material of Spatial Structures for Grade V Elementary School Students - Rizki Mutazam Ahmad; Armi Yuneti; Elya Rosalina (EDUJAVARE: International Journal of Educational Research, 2026)
This research was motivated by observations and interviews that indicated that students were less active in learning, easily bored, and had not achieved the learning objectives (KKTP). This study aimed to develop Augmented Reality-assisted Flash Card learning media for fifth-grade students in Sukamaju Elementary School. This study employed the Research and Development (R&D) method, and the ADDIE model, which consists of five development stages: analysis, design, development, implementation, and evaluation. The goal was to produce Augmented Reality-assisted Flash Card media designed to create more interactive and engaging learning experiences and enhance student active participation. The results showed that the use of Augmented Reality technology allows for realistic visualization of geometric objects, making it easier for students to understand abstract mathematical concepts. Therefore, this learning media is expected to assist educators in delivering material and increase student motivation, interest, and learning outcomes in geometric objects.